2018
DOI: 10.1007/s10971-018-4696-9
|View full text |Cite
|
Sign up to set email alerts
|

An optical catechol biosensor based on a desert truffle tyrosinase extract immobilized into a sol–gel silica layered matrix

Abstract: optical catechol biosensor based on a desert truffle tyrosinase extract immobilized into a sol-gel silica layered matrix. AbstractAn optical biosensor for the determination of catechol, a widely used yet toxic and carcinogenic molecule, is proposed using a crude extract of desert truffle (Terfezia leonis Tul.)as an enzymatic source of tyrosinase. The biosensor is constructed by the immobilization of tyrosinase crude extract in a bi-layered silica gel film prepared by dip-coating of an alkoxide/colloidal silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…As a general procedure, phenols 1 – 4 (0.02 mmol), tyrosinase (540 Units), and ascorbic acid (2 equiv), were placed in PBS 5.0 mL (0.1 M) at 25 °C for 24 h, and the mixture was stirred under O 2 atmosphere. In agreement with previous optimization studies reported in the literature, the experiments have been performed at optimal pH 7.0 [ 43 ]. Oxidations were performed using homogeneous and heterogeneous conditions.…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…As a general procedure, phenols 1 – 4 (0.02 mmol), tyrosinase (540 Units), and ascorbic acid (2 equiv), were placed in PBS 5.0 mL (0.1 M) at 25 °C for 24 h, and the mixture was stirred under O 2 atmosphere. In agreement with previous optimization studies reported in the literature, the experiments have been performed at optimal pH 7.0 [ 43 ]. Oxidations were performed using homogeneous and heterogeneous conditions.…”
Section: Methodssupporting
confidence: 79%
“…The K m and V max values measured for catalysts I – IV were of the same order of magnitude as those recently reported for the tyrosinase crude extract of desert truffle ( Terfezia leonis Tul.) after immobilization into a sol-gel silica layered matrix [ 43 ]. In this latter case, catalyst IV showed a K m value (0.25 mM) lower than that observed after the sol-gel encapsulation procedure.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Different enzymes have been used for biosensors construction, tyrosinase and laccase being among the most used ones. [12][13][14] In contrast to other enzymes, for example, horseradish peroxidase, [15] laccase catalyzes the oxidation of catechol by molecular oxygen, not requiring additional oxidation mediators like hydrogen peroxide, [16] which results in simplification of biosensor design.…”
Section: Introductionmentioning
confidence: 99%
“…The biosensor exhibited a linear response on catechol, but a decreased efficiency upon repetitive use, likely due to enzyme leaching or inactivation. Furthermore, the biosensor was not sensitive enough to the concentration of catechol as the limit of detection was 52 µM, in the upper limit of the acceptable concentration of phenolic compounds in wastewater [66].…”
Section: Enzyme Encapsulation In Silica Gels For Protein Delivery Bimentioning
confidence: 99%
“…These values are significantly different than those obtained for the soluble enzyme (K M = 2.5 mM and V max = 102 µM•min −1 ). These findings suggest that the gel matrix has stabilized an enzyme conformation that binds tightly the substrate, but is less able to catalyze the oxidation of catechol [66]. A bi-bilayer of encapsulated enzyme was used for the development of a biosensor for detecting catechol, which is a well known pollutant.…”
Section: Enzyme Encapsulation In Silica Gels For Protein Delivery Bimentioning
confidence: 99%